Impact in stability during sequential CDR grafting to construct camelid VHH antibodies against zinc oxide and gold. (22nd January 2018) - Saito, Ryota; Saito, Yutaro; Nakazawa, Hikaru; Hattori, Takamitsu; Kumagai, Izumi; Umetsu, Mitsuo; Makabe, Koki
Abstract: Biomolecules which recognize inorganic materials and metal surfaces gain much attention for creating new type of nanomaterials and sensors. 4F2, a camelid VHH antibody, recognizes ZnO surface and has been applied for sensor applications. 4F2 was constructed sequential complementarity determining region (CDR) replacement on the parental VHH antibody, termed the Construction of Antibody by Integrating Grafting and Evolution Technology; CAnIGET procedure. Here, we evaluate the influence of CDR replacements during 4F2 generation using calorimetric technique. We found that the initial peptide grafting at CDR1 results in the stability reduction and subsequent CDR3 randomize and selection restore the stability during the construction of 4F2. Further examination using anti-gold VHH, AuE32, revealed that the final CDR3 randomize and selection step has little effect in stability while the initial CDR1 grafting reduces the stability as same as the case for 4F2. Our results showing here provide the detailed view of the stability alteration during the CAnIGET procedure.